Anhedonia as a clinical correlate of inflammation in adolescents across psychiatric conditions. (21st October 2019) - Freed, Rachel D.; Mehra, Lushna M.; Laor, Daniel; Patel, Manishkumar; Alonso, Carmen M.; Kim-Schulze, Seunghee; Gabbay, Vilma
Abstract: Objectives: Peripheral inflammation has been associated with multiple psychiatric disorders, particularly with depression. However, findings remain inconsistent and unreproducible, most likely due to the disorder's heterogeneity in phenotypic presentation. Therefore, in the present study, in an effort to account for inter-individual differences in symptom severity, we utilised a dimensional approach to assess the relationships between a broad panel of inflammatory cytokines and key psychiatric symptoms (i.e. depression, anhedonia, anxiety, fatigue and suicidality) in adolescents across psychiatric disorders. We hypothesised that only anhedonia (reflecting deficits of reward function) will be associated with inflammation. Methods: Participants were 54 psychotropic medication-free adolescents with diverse psychiatric conditions and 22 healthy control (HC) adolescents, aged 12–20. We measured 41 cytokines after in vitro lipopolysaccharide stimulation. Mann-Whitney U and Spearman correlation tests examined group comparison and associations, respectively, while accounting for multiple comparisons and confounds, including depression severity adolescent. Results: There were no group differences in cytokine levels. However, as hypothesised, within the psychiatric group, only anhedonia was associated with 19 cytokines, including haematopoietic growth factors, chemokines, pro-inflammatory cytokines, and anti-inflammatory cytokines. Conclusions: Our findings suggest that general inflammation may induce reward dysfunction, which plays a salient role across psychiatric conditions, rather than be specific to one categorical psychiatric disorder.